Produtividade de cana-de-açúcar sob adubação com torta de filtro enriquecida com fosfato solúvel - Santos, Diego Henriques [UNESP]; Tiritan, Carlos Sérgio; Foloni, José Salvador Simoneti; Fabris, Luciana Boulhosa (My University, 2010)
Phosphorus is considered an essential element for plants and it is found in small amounts in Brazilian soils. The filter cake residue, composed of a mixture of bagasse and decanting sludge, has high levels of organic matter, phosphorus and calcium. The phosphorus present in the filter cake is organic, and its release, as it happens to the nitrogen, occurs gradually by mineralization and by microorganisms attack in the soil. This study aimed to evaluate sugarcane vegetative growth and yield under fertilization with filter cake enriched with soluble phosphate. The experiment was carried out in Presidente Prudente, São Paulo State, Brazil, by using a randomized complete block design, in a 5x4 factorial scheme, where the first factor consisted of filter cake doses (0 t ha-1, 0.5 t ha-1, 1.0 t ha-1, 2.0 t ha-1, and 4.0 t ha-1) and the second of phosphorus fertilizer doses (0 kg ha-1, 50 kg ha -1, 100 kg ha-1, and 200 kg ha-1 of P 2O5), with 4 repetitions, totalizing 80 plots. The experiment evaluated the tiller number, at 30, 60, 90, and 120 days after planting, oBrix, and yield. The stalk yield and tillering were influenced by the filter cake rates applied to the soil. Filter cake doses and their combination with phosphate did not change the juice quality (Brix) at harvest.
Sugarcane yield under fertilization with filter cake enriched with soluble phosphate
Keywords: Organo-mineral fertilizers; Saccharum spp.; Triple superphosphate; Saccharum